What an owl knows : [large type] the new science of the world's most enigmatic birds - Ackerman, Jennifer, 1959- (Center Point Large Print, 2023)
"Jennifer Ackerman illuminates the rich biology and natural history of owls and reveals remarkable new scientific discoveries about their brains and behavior. She joins scientists in the field and explores how researchers are using modern technology and tools to learn how owls communicate, hunt, court, mate, raise their young, and move about from season to season. We now know that the hoots, squawks, and chitters of owls follow sophisticated and complex rules, allowing them to express not just their needs and desires but their individuality and identity. Ackerman brings this research alive with her own personal field observations about owls and dives deep into why these birds beguile us ... an ... exploration of owls across the globe and through human history, and a spellbinding account of their astonishing hunting skills, communication, and sensory prowess. "--